Jigsaw Cooperative Learning as an Interactive Classroom Strategy for Fostering Students’ Learning Interest - Astri Yuli Ramadhani; Sahiruddin; Basri Massoeng (EduLine: Journal of Education and Learning Innovation, 2026)
This study aimed to examine the effect of the Jigsaw cooperative learning model on students' learning interest at SMA Negeri 15 Bone. This study used a quantitative approach with an ex post facto design. The research population consisted of 373 tenth-grade students, from which a sample of 34 students was drawn using a simple random sampling technique. Data were collected through a Likert-scale questionnaire covering four indicators of the independent variable (group cooperation, individual responsibility, interaction and communication, and learning engagement) and four indicators of the dependent variable (enjoyment, involvement, interest, and attention), which were validated through product-moment correlation and Cronbach's Alpha (.836 for the Jigsaw variable and .846 for learning interest). The data were analyzed using descriptive statistics, normality and linearity tests, and simple linear regression with the assistance of SPSS 26. The results showed that the implementation of the Jigsaw model fell into the fairly good category (M = 65.29; SD = 4.98), while students' learning interest fell into the good category (M = 74.41; SD = 4.08). The regression analysis produced the equation Y = 29.061 + 0.695X, indicating an effect on students' learning interest. These findings suggest that the Jigsaw cooperative learning model is an effective alternative strategy for enhancing students' learning interest at the senior high school level.